Fosphenytoin for seizure prevention in childhood coma in Africa: a randomized clinical trial. - Gwer, SA; Idro, R; Fegan, G; Chengo, E; Mpoya, A; Kivaya, E; Crawley, J; Muchohi, SN; Kihara, M; Ogutu, B; Kirkham, F; Newton, C (2013)
PURPOSE: We conducted a double-blind trial to determine whether a single intramuscular injection of fosphenytoin prevents seizures and neurologic sequelae in children with acute coma. METHODS: We conducted this study at Kilifi District Hospital in coastal Kenya and Kondele Children's Hospital in western Kenya. We recruited children (age, 9 months to 13 years) with acute nontraumatic coma. We administered fosphenytoin (20 phenytoin equivalents/kg) or placebo and examined the prevalence and frequency of clinical seizures and occurrence of neurocognitive sequelae. RESULTS: We recruited 173 children (median age, 2.6 [interquartile range, 1.7-3.7] years) into the study; 110 had cerebral malaria, 8 had bacterial meningitis, and 55 had encephalopathies of unknown etiology. Eighty-five children received fosphenytoin and 88 received placebo. Thirty-three (38%) children who received fosphenytoin had at least 1 seizure compared with 32 (36%) who received placebo (P = .733). Eighteen (21%) and 15 (17%) children died in the fosphenytoin and placebo arms, respectively (P = .489). At 3 months after discharge, 6 (10%) children in the fosphenytoin arm had neurologic sequelae compared with 6 (10%) in the placebo arm (P = .952). CONCLUSION: A single intramuscular injection of fosphenytoin (20 phenytoin equivalents/kg) does not prevent seizures or neurologic deficits in childhood acute nontraumatic coma.